Harmonization of Abortion Settings in Indonesia - Bayu Anggara; Made Gde Subha Karma Resen (Musamus Law Review, 2019)
This study is entitled Harmonization of Abortion Law in Indonesia. Abortion today is not something that is taboo to discuss and talk about, because abortion has occurred everywhere. Abortion is a health issue that is gaining attention nowadays in Indonesia. The regulation of abortion in Indonesia is regulated by 2 (two) Laws namely the Criminal Code and the Health Law, which is where there is a conflict of norms that the Criminal Code prohibits loopholes for abortion by anyone and under any conditions. While the Health Act provides space for abortions for women with pregnancies that endanger their lives and women with pregnancies due to rape. The problem of this writing is related to the harmonization of abortion arrangements in Indonesia and abortion arrangements in the future. This research was conducted by normative legal methods. Harmonization of abortion arrangements in Indonesia is resolved with legal theory, namely the Lex Specialis Derogat Legi Generalis legal theory, meaning that if there is an abortion case in Indonesia then the source of reference or legal basis is the Health Act because it is more specific than the Criminal Code. Abortion arrangements in Indonesia in the future in the form of a Penal Code also touches on the aspect of abortion which is regulated in Article 589 to Article 592 and remains on the concept to prohibit abortion by anyone and under any conditions.